2023
DOI: 10.3390/ani13081418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Concentrate-Induced Subacute Ruminal Acidosis Severity on Claw Health in First-Lactation Holstein Cows

Abstract: This study aimed to evaluate the effects of diet-induced subacute rumen acidosis (SARA) severity during transition and the early lactation period on claw health in 24 first-lactation Holstein heifers. All heifers were fed a 30% concentrate (in dry matter) close-up ration three weeks before calving, then switched to a high-concentrate ration (60% dry matter), which was fed until the 70th day in milk (DIM) to induce SARA. Thereafter, all cows were fed the same post-SARA ration with around 36% concentrate in dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The lacking influence of SARA-type on lying behavior seems explainable by the slow and insidious pathogenesis of feeding-induced laminitis that leads to extended lying durations of dairy cows ( Nocek, 1997 ). Indeed, changes in lying behavior on a short-term perspective are uncommon ( DeVries et al, 2009 ), but we recently reported poor claw health in primiparous dairy cows around 3 mo after the high-grain feeding period ( Kofler et al, 2023 ). Thereby, high SARA severity was associated with higher incidences of lameness and white line lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lacking influence of SARA-type on lying behavior seems explainable by the slow and insidious pathogenesis of feeding-induced laminitis that leads to extended lying durations of dairy cows ( Nocek, 1997 ). Indeed, changes in lying behavior on a short-term perspective are uncommon ( DeVries et al, 2009 ), but we recently reported poor claw health in primiparous dairy cows around 3 mo after the high-grain feeding period ( Kofler et al, 2023 ). Thereby, high SARA severity was associated with higher incidences of lameness and white line lesions.…”
Section: Discussionmentioning
confidence: 99%
“… Penner et al (2007) used the magnitude of the pH drop to characterize the severity of rumen acidosis, such as ruminal pH between 5.5 and 5.8 indicating mild SARA, between 5.2 and 5.5 indicating moderate SARA, and ruminal pH < 5.2 indicating acute rumen acidosis. Research has suggested that SARA increases the odds of systemic inflammation, laminitis, abomasal displacement, perturbed liver function, and milk fat depression ( Humer et al, 2018 ; Plaizier et al, 2018 ; Kofler et al, 2023 ), and this makes SARA a serious metabolic disorder in dairy cattle. It has also been shown that the risk of SARA is especially high during the first weeks after parturition, when cows are abruptly fed high-grain diets and their rumen is not yet adapted, coupled with the stressors of endocrine and metabolic changes, milking, rehousing, or potential postpartum complications ( Penner et al, 2007 ; Vergara et al, 2014 ; Zebeli et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%